2009
DOI: 10.1146/annurev-soc-070308-115958
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Attainments of Asian Americans

Abstract: According to the majority-minority paradigm, racial and ethnic minorities have lower socioeconomic characteristics than whites owing to discrimination. Asian Americans defy this conventional view, however, at least on average. Asian Americans tend to have higher mean levels of educational achievements, and several recent studies indicate approximate parity with whites in most arenas of the labor market for those Asian Americans who were schooled in the United

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
219
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(227 citation statements)
references
References 73 publications
8
219
0
Order By: Relevance
“…As already discussed above, Black respondents born in Africa, Latin America, or the Caribbean or who would identify a national origin there experience better educational outcomes than African Americans whose families have lived in the United States for several generations. Also, there is nontrivial variability in educational expectations and attainment of Asian Americans based upon national origin (see, e.g., Sakamoto, Goyette, & Kim, 2009). Goyette and Xie (1999) reported that the expectation of graduation from college is almost 30%…”
Section: Resultsmentioning
confidence: 99%
“…As already discussed above, Black respondents born in Africa, Latin America, or the Caribbean or who would identify a national origin there experience better educational outcomes than African Americans whose families have lived in the United States for several generations. Also, there is nontrivial variability in educational expectations and attainment of Asian Americans based upon national origin (see, e.g., Sakamoto, Goyette, & Kim, 2009). Goyette and Xie (1999) reported that the expectation of graduation from college is almost 30%…”
Section: Resultsmentioning
confidence: 99%
“…the Vietnamese-tended to be highly educated due to the selective stipulations of the 1965 Immigration Act (Sakamoto and Xie, 2006). Table 5 contrasts with the evolution of the educational position of the black population, discussed earlier, which also got better, but started at much lower levels and improved less at the higher education levels.…”
Section: Malay/chinese Inequalities In Malaysiamentioning
confidence: 85%
“…While during the first half of the century, 'Asians were concentrated at the bottom of the economic ladder, restricted to retailing, food service, menial service, and agricultural occupations', in modern-day America they are well represented in the 'well-paid, educated, white-collar sector of the workforce' (Espiritu, 1996, p.65). For instance, Sakamoto and Xie (2006) show that 33% of the male Asian Americans are employed as 'professionals' ('highly skilled occupations that typically require specialized training or licensed accreditation'), compared to 21% of the whites and only 13% of the African Americans. Although it is often claimed that Asian Americans are discriminated against when it comes to the managerial level and positions, Sakamoto and Xie (2006) also show that there is only a slight difference in managerial employment between whites and Asian Americans (8% for whites versus 7% for Asian Americans).…”
Section: Many Of the Highly Educated Asian Americans Who Arrived Aftementioning
confidence: 99%
See 1 more Smart Citation
“…However, other researchers argue that this group does face economic discrimination (e.g., Wong, 1982). Sakamoto, Goyette and Kim (2009) pointed out that the "high socioeconomic achievement among Asian Americans is misleading or highly exaggerated because racial and ethnic discrimination persists and many Asian Americans continue to be poor or disadvantaged" (p. 260). The Asian American population, currently inadequately studied, is growing faster than the overall population CHAPTER 18 27 (Bernstein, 2004).…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%